Bioprocesses in biotechnology: use of bioreactors for the production and scaling of products of commercial interest - Rosales-López, Catalina (2019)
Amongst the laboratories at the Biotecnology Research Center (CIB) of Costa Rica Institute of Technology (TEC), is the Bioprocesses Laboratory. This area involves all the lines of action of CIB, using bioreactors or temporary immersion bioreactors to grow microorganisms (bacteria, fungi and yeasts), plant cells, microalgae and animal cells with a common goal: the mass production of cells or bioactive compounds, becoming an effective tool for micropropagation, since it increases the multiplication coefficient and improves the quality of the material regenerated in vitro. The use of these systems reduces the costs in scale farming, which has been widely documented in a large number of species of commercial value. On the other hand, several culture conditions can be controlled in these systems, such as pH, agitation, dissolved oxygen and foam production. The CIB has four bioreactors for research, ranging from 250 mL, 3 L and up to 7 L. This article summarizes some of the projects which have studied plants and microorganisms in bioreactors at CIB.